MOBILE-CONTROLLED TIGHT COUPLING MECHANISM FOR INTERNETWORKING ARCHITECTURE OF UMTS AND WIRELESS LAN NETWORKS - AZIZ, ASIF (2015)
The Fourth Generation of Mobile and Wireless Networks (4G MWNs) is presume to be a unified network which comprises of numerous existing MWNs such as Wireless Local Area Network (WLAN), Global System for Mobile (GSM), Universal Mobile Telecommunications System (UMTS), Worldwide lnteroperability for Microwave Access (WiMAX), and satellite network etc, In 4G, MWNS the Mobile and Wireless Users (MWUs) are authorized to roam across assorted integrated MWNs, To keep the seamless call continuity in such an internetworking environment, is the most challenging issue, The literature revealed that when the MWU switches the active call between the dissimilar MWNs, the loose coupling mechanism lack in providing the seamless mobility, Conversely, by implementing significant modifications in the existing network architectures and protocols, the very tight coupling mechanisms efficiently address the seamless mobility.